GENETIC DIVERSITY IN ACCESSIONS OF INDIAN TURMERIC (CURCUMA LONGA L.) USING RAPD MARKERS - Ashraf, Kamran; Ahmad, Altaf; Shah, Syed Adnan Ali; Mujeeb, Mohd (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: The present investigation was undertaken for identification and assessment of eight accessions of Curcuma longa collected from all ecological zones in India by random amplification of polymorphic DNA (RAPD) markers. Methods: DNA was isolated using modified cetyl trimethyl ammonium bromide (CTAB) method. Polymerase chain reaction (PCR) was performed according to the method based on Williams et al. and data analysis was done using Alpha Imager EC software. Results: Eleven out of twenty primers screened were informative and produced 150 amplification products among which 132 products (88%) were found to be polymorphic. The percentage polymorphism of all 08 accessions ranged from 44.44% to 100%. A total of 150 amplification products were scored with an average frequency of 13.63 bands per primer. Most of the RAPD markers studied showed a different level of genetic polymorphism. The data of 150 RAPD bands were used to generate Jaccard's similarity coefficients and to construct a dendrogram by means of UPGMA. Conclusion: Results shows that C. longa undergoes genetic variation due to a wide range of ecological conditions within distribution area of its population in India. This investigation as an understanding of the level and partitioning of genetic variation within the accessions and would provide an important input into determining efficient management strategies and will help to breeders for turmeric improvement program.